Western Interior Cretaceous - Caldwell, W. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1975)
Summary Cretaceous North America was divided throughout most of the period by the Western Interior seaway, which connected temperate waters to the developing Arctic Ocean and trop,cal waters of the opening Atlantic. Vast quantities of terrigenous clastic sediments, fed into the seaway from the Cordillera, accumulated in shallow waters during two, major, marine cycles of sedimentation. Widely distributed, rapidly evolving, invertebrate slocks and a reliable radiometric time-scale combine to produce an exceptionally refined stratigraphie system. Marginal-marine sand complexes, some of which have been used to establish model patterns of deltaic and interdeltaic sedimentation, record local and regional tectonic movements.